Indigenous Chicken Production in Kenya: A Review - Kingori, A.M.; Wachira, A.M.; Tuitoek, J.K. (International Journal of Poultry Science, 2010)
Indigenous chickens in Kenya are about 22 million and are kept by 90% of the rural communities in small flocks of up to 30 birds mainly under free range system. The industry is flexible and does not require a lot of space. When people retire or are retrenched they easily start poultry keeping. Distinct indigenous chicken ecotypes have been identified and named. The names are phenotypic descriptions of the birds. The names used to describe the common phenotypes in Kenya are-frizzled feathered, naked neck, barred feathered, feathered shanks, bearded and dwarf sized. The local ecotypes of the chickens vary in body size, conformation, plumage colour and performance. The birds are hardy and thrive under a harsh environment with minimal inputs. They get most of their feed from scavenging and may occasionally benefit from kitchen and other household wastes. Eggs and chicken meat contribute to the protein nutrition of the rural population thus alleviating malnutrition. Sales of eggs and meat earn and diversify incomes for rural households especially among women and children who control benefits accruing from the enterprise. It has also helped those affected and infected by HIV Aids because it does not involve a lot of hard work. Indigenous chicken in Kenya are about 76 % of the total poultry population and produce about 55 and 47% of the total meat and eggs respectively. Productivity is low due to factors which include genotype, poor nutrition, diseases and management. Feed supplementation, provision of housing and disease control was found to improve growth rate and egg production.